Shariah Scheme for Port Infrastructure Development: A Bibliometric Review - Sri Rahardjo (SMART Insight, 2021)
Indonesia’s economic conditions over the last five years have shown high and stable growth. In addition to achieving satisfactory economic growth, there are several notes submitted by rating ratings. Indonesia’s economic growth becomes more optimal, namely the condition of Indonesia’s infrastructure, which is still inadequate. The existence of infrastructure is the most vital thing for the national economy. As the highest policyholder in a country, the government must provide the infrastructure needed by the community, such as energy, communication, and transportation. The development of transportation is directed at bridging the gap between regions and encouraging the equal distribution of development results. Sea transportation plays an important role in smooth trade because it has high economic value, carrying capacity, and relatively low cost. The Government of Indonesia has taken several steps in implementing its commitment to accelerate infrastructure development and encourage cooperation in infrastructure. However, this is experiencing funding constraints. Therefore, the government must evaluate and seek breakthrough sources and financing. One of the breakthrough sources of financing funds is by using Sukuk, Istishna, and Musyarakah. This study aims to determine the development trend of Istisna, Musyarakah, and Sukuk’s research on port infrastructure financing, published by leading journals on Islamic financial economics. The data analyzed consisted of 25 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of Istisna, Musyarakah, and Sukuk research developments on port infrastructure financing.